Survei Minat dan Kebutuhan Terhadap TV Berlangganan Di Jakarta - Ervan Ismail (Postgraduate of Jayabaya University, 2016)
This survey research is expected to describe the Pay TV indt!Stry, its custom er profile in Jakarta in the form of audience segmentation and the programs required and enthused by viewers. The research method was sun.'ey zeith sam ple of 2000 television owners as respondents. The sanzpli11g method in this1·esearch was Multistage Random Sampling from 5 (jive) out of6 OK/ Jakarta province area, excluding Thousand Islands Regency. Data collecting technique used was interview. There were only 228 respondents from 2000 samples wlztl subscribed Pa y TV The research result described the telei>isioll I'ieteer profile i11Jakarta through segmentation based on age, gender alld social en,nomytatu . An interesting finding was the capability of Pay TV companies· marketing 11s factors to acquire more subscribers with a total percentage of 32.5%. Tile mostinteresting program category depends on Pay TV subscriber is entertainment.Motion western pictures became the most favorite program, follo<eed by other countries' animation or cartoon category. Pay TV category in jakarta is domi llated by Satellite Pay TV.